APPLICATION OF METHOD OF SPATIAL DESCRIPTIONS FOR STUDY OF TENSE-DEFORMATION BEING OF THE GRABBED BORING COLUMN UNDER ACTION OF EXPLOSIVE WAVE - Мойсишин, Василь Михайлович; Яцишин, Василь Дмитрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article the method of spatial descriptions R. Clifton is adapted for the decision of axes symmetrical tasks of dynamic resiliency. A calculation became practical embodiment of method of the tense-deformation being of free and grabbed boring columns under action of explosive wave on the internal wall of pipe.